2010
DOI: 10.1590/s0104-11692010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Biological risk in nursing care provided in family health units

Abstract: There is very frequent exposure to potentially contaminated material in procedures performed by nursing professionals. This exploratory and descriptive study characterizes the potential risk of biological exposure in procedures performed by nursing professionals in ten Family Health units in São Carlos-SP, Brazil. We observed 238 procedures involving potential risk of contact with biological material, in which more than 90% involved the use of needles. The average rates of adherence to standard precautions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…However, non-adherence to glove use and inappropriate disposal of lancets need to be addressed. A study conducted in Family Health Units in the same region corroborates these findings, reporting the use of lancets in 100% of the cases, appropriate disposal in 66.7% and the use of gloves in only 30.3% of the cases (17) .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, non-adherence to glove use and inappropriate disposal of lancets need to be addressed. A study conducted in Family Health Units in the same region corroborates these findings, reporting the use of lancets in 100% of the cases, appropriate disposal in 66.7% and the use of gloves in only 30.3% of the cases (17) .…”
Section: Discussionmentioning
confidence: 55%
“…Deciding how to clean hands (soap, antiseptic soap or alcohol) should take into account the type of contact, degree of contamination, the patient's conditions and procedure(s) to be performed (22) . However, despite the many ways available to wash hands, studies show that health workers respond in a dissatisfying manner to hand washing recommendations (7,17) ; they fail to perform hand washing in 60% of the occasions it is indicated as needed (22) .…”
Section: Discussionmentioning
confidence: 99%
“…This work process determines different occupational health risks that can lead to workers' physical and/or mental illness, including biological risks (10)(11)(12) . Hence, adherence to vaccination against hepatitis B should be considered in the context of FHS workers' healthdisease process, including the study of variables that can be associated with different health behaviors, such as sociodemographic, lifestyle, health condition and occupational variables.…”
Section: B Include Health Professionals In Specific Areas Likementioning
confidence: 99%
“…Another study demonstrated that in a PHC setting hand hygiene was rarely performed before care, ranging from 8% to 53.3% depending on the type of procedure; and after procedures such as capillary blood glucose monitoring only in 20% of instances. In intravenous medication administration, 53.3% washed hands prior to the procedure and 27.3% after that [27]. Nonetheless, this low compliance does not seem to be restricted to Brazil or indeed other low-middle income countries.…”
Section: Discussionmentioning
confidence: 99%